The Discovery of Novel Protein Tyrosine Phosphatase ε Inhibitors Using a High‐throughput Screening Approach. (January 2017) - Yun, Hye‐Yeoung; Ku, Bonsu; Lee, Hye Seon; Shin, Ho‐Chul; Park, Jun‐Beom; Kim, Chang Hyen; Kim, Seung Jun
Abstract : Protein tyrosine phosphatase epsilon (PTPε) is important for signal transduction in osteoclasts, and is considered to be an attractive drug target for the treatment of osteoporosis. We identified 11 potent PTPε inhibitors based on three chemical scaffolds through the high‐throughput screening of a chemical library. As these compounds are structurally diverse with high bioavailability, they warrant further investigation in the near future. The discovery of these inhibitors and the relationship between their structure and inhibitory activity toward PTPε is discussed in detail. Abstract :